TRANSFORMING BUSINESS MODELS: INNOVATIONS FROM AGRICULTURE TO AQUACULTURE - Jia-Ru Lin; Te-Tsai Lu (Graduate Program of Universitas Tarumanagara, 2026)
Taiwanese agriculture has long been under pressure from climate change, labor shortages, and volatile market prices. Smallholders often remain in a weak bargaining position due to limited scale, making it difficult to stabilize output and accumulate added value. Using a qualitative case study approach, the present study examines the transformation of a greenhouse muskmelon farm from 2019 to 2025 and synthesizes a six-stage innovative operating model consisting of (1) technological adoption, (2) grading and packaging, (3) channel development, (4) supply-demand planning, (5) team organization and division of labor, and (6) brand building. The findings show that facility-based cultivation and precision management reduce climate risks and improve product consistency; standardized grading and packaging enhance product identification and market trust; and access to wholesale channels and market intelligence enables the case to shift from a price taker to a supply-chain coordinator. Team-based aggregation and staggered production increase shipment volumes and bargaining power, while branding and traceability help the product enter mid-to-high-end markets and capture price premiums. The proposed model is further transferred to and validated in a hard clam aquaculture case. Results indicate that smart water-quality monitoring, standardized grading and packaging, diversified channels, and staged harvesting improve survival rates, stabilize cash flow, and strengthen brand trust. Overall, the six-stage model demonstrates cross-industry transferability and provides a practical reference for enhancing resilience and sustainable competitiveness among small-scale farmers and aquaculture operators in Taiwan.